Direct Instruction vs. Computer Simulation and their Learning Outcome in Engineering Education - Andreas zendler; Manuel Gohl (International Journal of Engineering Education, 2019)
Answers to the questions of which instructional methods are suitable for school, what instructional methods should be applied in teaching individual subjects and how instructional methods support the act of learning represent challenges to general education and education in individual subjects. This study focuses on the empirical examination of learning outcome in engineering educationwith respect to two instructional methods: direct instruction and computer simulation. A CRF 2x2 design is used to control instructional method and class context. Learning outcome on bridge construction is assessed with reference to the optics of bridge and the material usage for the bridge. The empirical findings show that learning with direct instruction was superior to computer simulation.